1995
DOI: 10.1007/bf02063257
|View full text |Cite
|
Sign up to set email alerts
|

Rebamipide, novel prostaglandin-inducer, accelerates healing and reduces relapse of acetic acid-induced rat gastric ulcer comparison with cimetidine

Abstract: This study was done to elucidate whether rebamipide during the initial period of acetic acid-induced gastric ulcer affected healing and future ulcer relapse. The cumulative healing rate was higher in rats given rebamipide alone or those given rebamipide and cimetidine during and after administration, but not in rats given cimetidine alone, compared to control rats. Cumulative relapse rate was significantly lower in rats initially given rebamipide alone or those given rebamipide and cimetidine than in rats init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 11 publications
3
40
0
Order By: Relevance
“…There are only a few reports on the recurrence of ulcer after healing in experimental models. Arakawa et al [23,24] reported that the cumulative recurrence rate was about 30% (cumulative nonrecurrence rate 70%) on the 90th day after ulcer induction in the acetic acid-ulcer model. The differences in the cumulative recurrence rates between Arakawa's and this study might depend on the difference in the intensity of the ulceration, as on the 150th their cumulative healing rate was high in comparison with that of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a few reports on the recurrence of ulcer after healing in experimental models. Arakawa et al [23,24] reported that the cumulative recurrence rate was about 30% (cumulative nonrecurrence rate 70%) on the 90th day after ulcer induction in the acetic acid-ulcer model. The differences in the cumulative recurrence rates between Arakawa's and this study might depend on the difference in the intensity of the ulceration, as on the 150th their cumulative healing rate was high in comparison with that of this study.…”
Section: Discussionmentioning
confidence: 99%
“…But it remains unclear why prolonged treatment with FRG-8813 did not cause the rebound hyperacidity, as famotidine and cimetidine did not induce hypergastrinemia either. On the other hand, it has also been postulated that a decrease in gastric defensive factors resulted in ulcer recurrence [11], and that treatment with a gastroprotective drug, increasing the levels of gastric defense factors, and H 2 -receptor antagonist is beneficial for obtaining a good QOUH and reducing ulcer recurrence [23]. Indeed, for prevention of ulcer recurrence a gastroprotective drug was used clinically with a H 2 -receptor antagonist, and a lower recurrence rate was shown for ulcers healed with combination therapy than for those treated with the H 2 -receptor antagonist alone [3,14].…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanism of action is not fully understood, though it appears to stimulate mucus secretion and PG synthesis [121] and to scavenge oxygen-derived free radicals [6] . It has been shown to significantly reduce the severity of NSAID-induced enteropathy in rats [122] .…”
Section: Nsaid-enteropathymentioning
confidence: 99%
“…[93][94][95][96][97] Penney et al 98) demonstrated that misoprostol reversed the delayed healing effect of aspirin via an effect on epithelial regeneration. Arakawa et al 99) examined the effects of rebamipide, a novel PG-inducer, on healing and relapse of acetic acid ulcers in rats. Arakawa found that rebamipide and rebamipide together with cimetidine resulted in a higher healing rate and a lower cumulative relapse rate compared to control groups.…”
Section: Mucosal Defensive Drugsmentioning
confidence: 99%